Improving speaking skill for technical students at IUH through experiential activities - Minh, Nhat Truong Tran; Kim, Oanh Duong Thi (Linguistics and Culture Review, 2021)
Nowadays, English is one of the most important languages in Vietnam, so students at all levels in Vietnam have been studying English as a compulsory subject with special attention to speaking skills to communicate and work in the integration world. However, speaking skill is still strongly not successful with students, especially technical students at universities. Therefore, this small-scale research aims to investigate the difficulties which technical students at IUH usually faced when practicing the skill, and the efficiency of experiential activities in improving learners’ speaking skills. This research used quasi-experimental method. The sample of the research is 120 technical students in 4 English classes in the second semester of the school year. After distributing a questionnaire to 120 technical students at IUH, the findings indicated that speaking skill is essentially evaluated by most of the students, although they still have some difficulties when practicing. It was also evident that students were interested in experiential activities which were applied to improve students’ skills, such as watching films and telling opinions, role play, communicate in group work, and so on. These activities not only enhance students’ positive motivation in studying English and speaking skills but also improve their communicative skills.